Análise fotoelástica em modelos com implantes distais angulados em uma reabilitação tipo protocolo - Ferreira, Mário Serra (2012)
The aims of this study were to investigate the peri-implant stress fields generated by five different configurations in a mandibular rehabilitation through the application of vertical load on the cantilever by the photoelasticity technique and to test the hypothesis that the reduction in cantilever length by the tilted of the implant decreases the stress gradient (1), and that the use of tilted abutments also favors the stress distribution (2). For the above were made five intermediate tapered low profile metal structures, attached to 13 mm by 3.75 mm external hexagon type implants, simulating different configurations of a rehabilitation protocol type Branemark and embedded in resin for photoelastic analysis tensions. A qualitative and quantitative evaluation of the fringe orders and the shear stress was conducted in 27 points located around the implants through a load applied vertically in two parts of the cantilever. The groups differed among themselves by varying the tilting of the distal implant at 0° (group GC), 17° (group G17) and 30° (group G30),as well as the variation of the straight and angled intermediates. Data was evaluated using analysis of variance test (ANOVA) and Tukey's test for parametric groups (P <0.05). Significant statistical differences were found among the groups. Sites under higher stress were found in the distal implants in the cervical and apical regions. The groups that presented lowest stress were 30° tilted (G30A) and 17° tilted (G17A). The ones that reached highest levels of peri-implant tension were 17o straight (G17R) and and 0° (GC). The tilting of 30° in the distal implants offers mechanical advantage, resulting in a decrease of peri-implant stress. The use of tilted micro-units offered lower tensions between the groups.